Dynamical complexity in Swarm electron density time series using Block entropy. (2nd November 2020) - Balasis, G.; Papadimitriou, C.; Boutsi, A. Z.; Daglis, I. A.; Giannakis, O.; Anastasiadis, A.; De Michelis, P.; Consolini, G.
Abstract: Our goal in this study is to investigate the dynamical complexity of the electron density profiles in the topside ionosphere as measured by the Swarm mission, employing the use of symbolic information-theoretic techniques. We perform a Block entropy analysis for a time interval associated with the most intense magnetic storm of solar cycle 24, which occurred on 17 March 2015. We produce entropy maps for varying degrees of magnetospheric disturbance, resolving the different effects that the various geomagnetic activity levels have in the dynamics of the complex magnetosphere-ionosphere coupling system. Understanding the impact of these effects on the ionospheric plasma constitutes a crucial factor for the functionality of the modern technological infrastructure operating around the Earth and, thus, human welfare.